Essentials of Engineering Thermodynamics : Principles and Applications - Kleinstreuer, Clement (McGraw-Hill Education, 2021)
The main objective here is to develop an engaging textbook that improves on existing undergraduate thermo-books in several categories. Ultimately, it will result in students? higher success, i.e., a more substantial knowledge base and independent problem-solving skills.